A meta-analysis of treatment of vestibular schwannoma using Gamma Knife radiosurgery - Rykaczewski, Bartosz; Zabek, Miroslaw (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : One of the alternative methods of surgical treatment of vestibular schwannoma is Gamma Knife radiosurgery. The purpose of this metaanalysis was to analyze the progress in treatment of vestibular schwannoma using Gamma Knife radiosurgery based on data in the literature of the last five years. Material and methods: In the collected English-language literature from the years 2007–2011, contained in 20 scientific journals, clinical articles of many years study at a single center were extracted and also review papers and case reports. The main criteria of our own analysis were: patient age, tumor size, the dose in Gy, the time from surgery to follow-up, the degree of tumor growth inhibition, and hearing preservation. For statistical calculations comparing series of studies we used nonparametric analysis of variance and tests at the significance level of p > 0.05. Results: The 46 evaluated clinical articles show the results of studies over many years. A comparison of the results of the analysis made on the basis of papers published in the period 1998-2007 with the results of the current series from the period 2007–2011 allowed us to establish that the average dose applied to the periphery of the tumor was lower (12.4 Gy) than in the earlier series of 1998–2007 (14.2 Gy), and hearing preservation was higher (66.45% vs. 51.0%). Conclusions : Clinical findings widely documented in the literature over the past five years indicate the progress in treatment of vestibular schwannoma using Gamma Knife radiosurgery.